Toward an optimum design of fractal sausage Minkowski antenna for GPS applications - Riyadh Khlf Ahmed; Israa Hazem Ali (Bulletin of Electrical Engineering and Informatics, 2022)
Fractal is one of the important tools to produce efficient and well-suited antennas for navigation systems. A novel design of broadband fractal sausage Minkowski antenna is described in this research article. Sausage Minkowski is designed and simulated for global positioning system (GPS) application that relies on fractal geometry using computer simulation studio microwave (CST MW) software. The substrate sheet is Roger TMM4 has of 4.5 dielectric constant and 1.6 mm altitude. A small metallic patch over a large metallic ground layer is made of perfect electric conductor (PEC) material. The suggested fractal antenna can be used efficiently in the military applications which demand a narrow spectrum and a tiny antenna profile. By introducing four various levels of fractal iteration models and compared each one to the other. The main aim of this work is to increase antenna gain and reduce the antenna size, in addition to improving the semi-flat voltage standing wave ratio (VSWR) with respect to decreasing the resonance frequency is. For 10% decrease in the frequency for the 3rd iteration value led to a clear improvement in the antenna characteristics such as directivity, gain, and VSWR. The reflection coefficient and bandwidth remain in range.